Growth and characterization of inosine crystals: a third order NLO single crystal. (10th November 2018) - Indumathi, P.; Chitravel, T.; Saravanan, R. R.; Vinitha, G.; Indra, K.
Abstract: A organic single crystal of Inosine have been grown from saturated solution by slow evaporation solution growth technique. The crystalline perfection of the grown crystal was accomplished by Single X-ray diffraction studies. The as grown single crystal exhibit monoclinic structure type, crystallizes in the space group of P21. The various functional groups present in the crystal was analyzed by FT-IR and FT-Raman studies. The optical transmission window of the grown crystal was found by UV–vis-NIR analysis. Thermogravimetric (TG) and differential thermal analysis (DTA) were carried out to characterize the thermal stability of the grown crystals. Theoretical vibraitonal frequencies are calculated from DFT-B3LYP gradiant calculations employing 6–31G(d, p) as a basis set. These datas are in good agreement with theoretical and experimental values of FT-IR, FT-Raman and UV–vis-NIR measurements. Third order nonlinear optical efficiency was examined using Z-scan technique.